2012
DOI: 10.1007/s00415-011-6370-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea linked to wake-up strokes

Abstract: Obstructive sleep apnea (OSA) has been considered as one of the risk factors for ischemic stroke, but the impact of OSA on wake-up stroke (WUS) is not well studied. We aimed to determine the relationship between OSA and WUS. We prospectively recruited 71 patients with mild to moderate ischemic stroke during hospitalization. Patients were classified into WUS and non-WUS. A full-night sleep respiratory study was performed between 3 and 14 days after stroke onset. Demographic data, sleep respiratory data, heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 35 publications
5
53
2
2
Order By: Relevance
“…Our study, as well as previous studies, confirmed the association of WUS with SDB, which is a treatable risk factor of vascular diseases. [17][18][19] Using respiratory polysomnography (Autoset Portable Plus II device) in 164 patients with diagnosis of acute stroke, Martinez Garcia et al found significantly higher AHI (33.3 vs. 24.7), greater nighttime desaturation, and a greater probability of SDB symptoms prior to stroke in strokes occurred during sleep or on waking compared to the strokes that occurred during the rest of the day. 18 Bassetti et al among 152 patients with acute ischemic stroke found age, diabetes mellitus, and nighttime stroke onset to be independent predictors of AHI.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, as well as previous studies, confirmed the association of WUS with SDB, which is a treatable risk factor of vascular diseases. [17][18][19] Using respiratory polysomnography (Autoset Portable Plus II device) in 164 patients with diagnosis of acute stroke, Martinez Garcia et al found significantly higher AHI (33.3 vs. 24.7), greater nighttime desaturation, and a greater probability of SDB symptoms prior to stroke in strokes occurred during sleep or on waking compared to the strokes that occurred during the rest of the day. 18 Bassetti et al among 152 patients with acute ischemic stroke found age, diabetes mellitus, and nighttime stroke onset to be independent predictors of AHI.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 Polysomnography is the gold-standard technique to diagnose sleep apnea and sleep-disordered breathing. However, it is not universally available and requires a sleep laboratory.…”
Section: July 2016mentioning
confidence: 99%
“…NOD was observed in 16.8% in our study, which was lower than the reported prevalence of sleep apnea after stroke using polysomnography. 6,7,9,23 In addition, we excluded patients treated with oxygen to minimize bias. This could have affected the lower rate of sleep-disordered breathing in our patients, despite the absolute numbers being small.…”
mentioning
confidence: 99%
See 2 more Smart Citations